Examining the Impact of Trust and Image on The Loyalty of Islamic Banking Clients in Indonesia: an Empirical Study - Hasdiansa, Ilma Wulansari (Economics and Business Journal (ECBIS), 2023)
Exploring the multifaceted dynamics of customer loyalty in Islamic banking, this study investigates the roles of trust and corporate image in Eastern Indonesia's Islamic banking sector. Employing structural equation modelling (SEM) as the analytical tool, the research uncovers the intricate interplay between corporate image, trust, and customer loyalty. Results indicate that a solid corporate image significantly and positively influences customer trust. This trust is crucial in boosting customer loyalty towards Islamic banking services. Highlighting the importance of corporate image, the study reveals its role as a cornerstone in building and reinforcing customer trust, which is crucial for fostering long-term customer relationships. The research provides strategic insights for Islamic banks in Eastern Indonesia, suggesting that a focus on enhancing corporate image and trust can lead to increased customer loyalty. This contribution enriches the understanding of loyalty dynamics within the Islamic banking sector, underscoring the significance of trust and corporate image in the unique market context of Eastern Indonesia.